PHYTOCHEMICAL ANALYSIS AND ANTIFUNGAL ACTIVITY OF SOME MEDICINAL PLANTS AGAINST ALTERNARIA SPECIE ISOLATED FROM ONION - R. Kalsoom; 2; M. S. Haider; S. Chohan2 (Journal of Animal and Plant Sciences, 2020)
Medicinal plants are the immense source of bioactive compounds and can be used for the treatment of various diseases of plants, animals and even human beings. Aim of the present study was to investigate the antifungal potency of leaf extracts of Citrus limon, Cassia fistula and Euclaptus camaldulensis against Alternaria specie associated with onion leaves through poisoned food technique. Based on the outcome of our results, methanolic leaf extracts of C. limon showed highest inhibition (61%) followed by C. fistula (53%) and E. camaldulensis (44%) respectively. Phytochemical analysis of best result oriented citrus extract was done with Gas Chromatography-Mass Spectrometry (GC-MS) technique. The results revealed the presence of antimicrobial compounds predominantly hexacosane (21.41%), delta-tocopherol (13.25%), gamma-tocopherol (9.61%), valproic acid (8.24%), gamma-sitosterol (3.98%), cetene (3.84%), isoquinoline,1-[(3,4-diethoxyphenyl)methyl]-6,7-diethoxy- (3.36%), nonadecanoic acid, methyl ester (3.05%), benzeneacetic acid (2.95%). Present study indicates that plant extracts could be a potential alternative in developing a potent plant-based fungicide which can be used in organic farming for the management of diseases in plants. Therefore, extensive research is required to detect more compounds in order to develop effective management approaches that significantly reduce the impact of the pathogens on human health as well as on environment.
Keywords: Antifungal potential; poisoned food technique; biologically active compounds; GC-MS analysis; Citrus limon